Um estudo de caso de desenvolvimento do back-end do amo (ambiente de monitoria on-line) - Alcântara, Pedro Henrique De Sousa (2025)
Considering the need to improve communication between higher education students, academic monitors, and professors, the development of the Ambiente de Monitoria Online (AMO) software was conceived by the Projeto de Apoio ao Ensino (PAE) at the Federal University of Ceará (UFC), Russas campus. The application aims to establish an additional means of contact among campus members, allowing students to ask questions about topics within their courses and enhance heir learning. The tool enables users to post comments in forums and schedule meetings with academic monitors. This work aims to present the development of the application’s back-end, which consists of a Representational State Transfer (REST) Application Programming Interface (API). To carry out this work, it was necessary to analyze the system requirements document, which contains all its functionalities. To meet these requirements, the system was developed using the Python programming language, with Django Rest Framework (DRF) to build the API following a Model-View-Controller (MVC) architecture. After the development phase, tests were conducted to verify whether the functionalities were correctly implemented and if they returned the expected and accurate data. The mobile application was launched for the academic community of Russas in February 2025. Upon receiving user feedback or identifying the need for improvements, the application will be updated to ensure good usability and efficiency for its users.